THE NATION AS A PROTAGONIST OF EDUCATION IN LATIN AMERICA (1870-1930) - Romo, Andrés Donoso (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
During the years in wich were celebrated the centenaries of the latin american countries, the nation and the education achieved big importance. In these pages will be exposed an interpretative proposal to understand how there were forging the processes which made possible the idea of the nation, the classrooms were filled of flags, and so there will be a determined expansion of the popular education as well as educational systems were created in all the region.